2017
DOI: 10.18632/oncotarget.15760
|View full text |Cite
|
Sign up to set email alerts
|

Association of immunologic markers from complete blood counts with the response to preoperative chemoradiotherapy and prognosis in locally advanced rectal cancer

Abstract: We investigated retrospectively whether immunologic markers from a complete blood count (CBC) are associated with the responsiveness to preoperative chemoradiotherapy (PCRT) and oncologic outcomes in 984 patients with locally advanced rectal cancer (LARC) who also underwent radical surgery from 2005 to 2013. CBC parameters including the neutrophil to lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR), and platelet to lymphocyte ratio (PLR) were recorded. Pathologic responses to PCRT were evaluated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 29 publications
0
27
2
2
Order By: Relevance
“…However, the predictive role of NLR in LARC patients remains unclear. Jung et al 29 . reported that pre-CRT NLR was not able to distinguish recurrence-free patients with rectal cancer receiving NCRT.…”
Section: Discussionmentioning
confidence: 99%
“…However, the predictive role of NLR in LARC patients remains unclear. Jung et al 29 . reported that pre-CRT NLR was not able to distinguish recurrence-free patients with rectal cancer receiving NCRT.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many clinicopathological and molecular factors have been suggested to be associated with pCR, although their utility in clinical practice remains controversial. 5 8 …”
Section: Introductionmentioning
confidence: 99%
“…Jung et al reported that patients with rectal cancer and high LMR, high PLR, or low NLR were associated with increased RFS, and high PLR was an independent marker for RFS after surgery following nCRT. However, no relationship to tumor response was found [23]. In the current study, we analyzed the relationships between PLR and treatment outcomes (tumor response, RFS) but did not find an association.…”
Section: Discussionmentioning
confidence: 76%
“…However, the NLR cutoff values used in previous studies of patients with rectal cancer that underwent nCRT were inconsistent. Some studies used historical values from other primary or metastatic cancers [12, 20, 25], and other studies used cutoff values calculated by statistical methods [23, 26, 27]. In the current study, cutoff values were determined after calculation by statistical methods.…”
Section: Discussionmentioning
confidence: 99%